Examination and treatment of lithiasis of the main bile duct in laparoscopic surgery - Praderi Gambardella, Luis A; Geninazzi, Héctor; Tchekmedyian, Vartan; Balboa, Oscar; Matteucci, Pablo; Voelker, Ricardo; Praderi, Luis A (Cirugía del Uruguay, 1995)
by means of videosurgery is one of the present challenges far laparoscopic biliar surgery. The authors analyse the incidence of lithiasis of the MBV in a series of 425 laparoscopic cholecystectomies carried out at the Hospital Italiano and Hospital Español in Montevideo between May 1991 and May 1994 and present their study and treatment in the pre, intra and postoperative phases. They discuss the use of retrograde endoscopic cholangiopancreatography and transcystic cholangiography. They a/so present different laparoscopic techniques far the extrae/ion of choledocian stones and propase an algorythm far stydy and treatment. The authors believe that future tendencies wi/1 consist of laparoscopic treatment of biliar lithiasis (gal/ bladder and choledocian) in a single stage where intraoperative echography, transcystic extrae/ion of choledocian stones and transcystic anterograde papillotomy wi/1 possibly have an importan/ place.